Motivation and Factors Affecting Pre-Service English Teacher in Joining Webinar Session - I Ketut Armawan; Gede Mahendrayana (Universitas Pendidikan Ganesha, 2023)
In the pandemic due to COVID-19, a massive online learning process is being carried out in education. This study aims to investigate types of motivation and identify factors that influence motivation among pre-service English teachers to participate in webinars as learning material in a distance learning context. This research is descriptive research using a mixed methods research design. The sample for this research consisted of 96 teachers. The methods used to collect data were questionnaires and interviews. The data collection instrument uses a questionnaire sheet and interview guide. The data was tabulated and analyzed quantitatively using descriptive statistical analysis to categorize the data and determine the percentage of data. The research results show that the motivation of pre-service English teachers is dominated by extrinsic motivation. It has a significant impact on student motivation to take part in webinars. Several important points about respondents' motivation for webinars are useful for increasing and enhancing their motivation for participating in webinars to increase professional development as prospective English teachers.